Analiza vpliva prometnega toka pešcev na prepustno zmožnost krožišča z uporabo diskretnih simulacij - Tollazzi, Tomaž (Strojniški vestnik, 2006)
Like with other non-traffic-lighted intersections, the capacity of roundabouts can be reduced by special traffic conditions. In such cases the pedestrian's and/or cyclist's traffic flow, crossing one or more roundabout arms, is the size that influences the roundabout filling or emptying. The purpose of this paper is to show how the use of discrete simulation methods contributes to the decision on implementing a roundabout, or to help decide if the roundabout is going to fulfil appropriately the condition of the expected flow of pedestrians and/or cyclists. A new approach is suggested for dimensioning roundabouts, with mathematical modelling of the traffic flows using the discrete simulation method, and considering the statistically evaluated entry data for vehicles' and pedestrians' traffic flows. The simulation results are useful when determining the capacity of foreseen and suggested roundabouts, which will function in different circumstances. The presented model derives from the expected time void in the vehicles' traffic flow, used by the pedestrians, assuming their right of way when joining the traffic. The simulation analysis was verified on a real example of a montage roundabout in Koroška Street in Maribor, where measurements of the motorised vehicles' traffic flow, and pedestrians' and cyclists' traffic flow were made.The procedure, shown in the paper, along with the scientific approach to mathematical modelling, presents a practical method, helpful when deciding whether to implement a roundabout in the case of heavy pedestrians' and/or cyclists' traffic flows.
Keywords: cestni promet; krožišča; prometni tokovi; simulacije; modeli